Brazil : equitable, competitive, sustainable, contributions for debate - The World Bank (Washington, DC : World Bank, 2003)
The information presented in this book is organized along five overarching themes: investing in people; improving productivity; managing natural resources; delivering government services to all; and stabilizing the economy. Part I brings contributions on education, health and social protection, and discusses human and social protection, and human and social capital challenges. Part II is focused on finance, infrastructure, private sector development, and innovation and technology issues, summing up the experience and views on physical capital and investment climate. Part III corresponds to natural capital and quality of life issues, bringing messages on forest use and conservation, rural development, natural resources, and urban and water services. Finally Part IV addresses the prerequisite for the other themes, analyzing conditions for macroeconomic stability, fiscal sustainability, and good governance."
Includes bibliographical references.
rpm 16/09/16
Loans
Keywords: Brazil -- Economic policy; Brazil --- Social policy; Economic development -- Social aspects; Political science -- Economic Conditions; Brazil